KEBI JAKAN DASAR PENDIDIMN MENU JU MASYARAKAT MADANI INDONESIA - Sumarno Sumarno (Jurnal Cakrawala Pendidikan, 1998)
The Indonesian people are now in a period of uncertainchange due to the severity of the crisis facing them. 'The crisishas touched the wheels of the eco~lomics, legal, and politicalsystems and is very likely to touch also other aspects such as thesocio- cultural and moral aspccts of living in a socicty, countryand nation. The society is changing from a dual systcni, in whichthe political system (as a structure) and the social system (as thesuperstructure) are separated fronl each other, towards a 11cwsystem, the so-called ciivil society, whiich is actually still one stepbefore Ihe elhical society. Uurilig the present period orstructural change, the quality of the hunlan resources must beprepared, since they are the main components in the culturalchange towards the intended civil society. If the proporlio~l ofeducated citizens is still too small, it may be very difficult for thecivil society to come into reality and even niore so Tor the ethicalsociety. 'Thercfore, there necds to be rcorientatioli in thedirection and basic policy of the national education to supportthe effort of the nation towards a civil society. The eduqtionalreorentation involves two aspects. Firstly, the characteristics orthe quality of the educated people suitable for the civils societyneed to be clarified and, secondly, at the macro-level there arereal needs for a more democratic educational system, withhctter access to educational opportunities, equality in quality,efficiency, productivity, and employability.